Investigation of adjustable valve of semi-active damper for improving ride comfort in a passenger car - Ahmed Mostafa, Mohammed Ragab (2019)
The suspension of a car is considered as an essential element in the vehicle. The primary function of the suspension system is to isolate the vehicle structure from shocks and vibration due to the irregularities of the road surface. Two primary objectives need to be satisfied which are ride comfort and road handling. Ride comfort is inversely proportional to the absolute acceleration of the vehicle body, while the road handling is linked to the relative displacement between the vehicle body and the tires. The thesis attempted to realize the damping force in twin and monotube by developing a mathematical model. The models show similar trends, while different forces are recorded, due to the pressure in the compression chamber increases during rebound in twin tube damper and a monotube damper the gas chamber is always connected to the compression chamber. Shock dyno testing is carried out to validate the model of twin tube with experiment data. A prototype of electronically adjustable semi-active shock absorber from available twin tube is developed, this achieved by attaching stepper motor for each shock absorber which helps in adjusting the bleed orifice to a particular position that alternates the hydraulic oil flow in the shock absorber between piston’s chamber during the process of compression and rebound. To evaluate the effect of the developed semi-active shock absorber on the dynamic behavior of the vehicle, several tests were carried out on different types of road condition (bumpy, straight-line and roundabout). These tests were used to evaluate the acceleration and ride quality. There is a great range in response when the bleed orifice is opened reached up to 35% between the stiff and soft setting. The value of root means square acceleration (RMS) was calculated and compared with the standard of human exposure to whole-body vibration, which shows an error of 6% slightly. The result shows the effect of the electronically controllable shock absorber on a vehicle’s dynamic behavior. The advantage of electronics to improve the performance of ride comfort and reduced the harms due to undesired vibration. To evaluate force generated by the developed model of the semi-active monotube damper on the dynamic behaviour of the vehicle, the model was analyzed and compared with the passive and On/Off sky-hook control strategy in the quarter car using two different types of road (random excitation, bumpy) as input to the quarter car model. Force hysteresis loop with different sets of orifice diameter was generated. PID controller design approach has been examined with CVD to evaluate semi active damper performance, where the combination shows a reduction in both body acceleration and vertical displacement contrasting with passive and On/Off sky-hook 73.4% and 53.8% respectively and also the selling time by 79% and 59% for a bumpy road. This considered an improvement toward the ride comfort and vehicle stability.